Influence of Mental Health, Turnover Intention And Work Environment On The Performance Of Millennial Employees at Bank BRI Branch Bengkulu - Rhaeny, Rhaeny; fauzan, fauzan; puspita, veny (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to analyze the influence of mental health, turnover intention, and work environment on employee performance among millennial employees at Bank BRI Bengkulu Branch. Methodology: The research employs a quantitative approach with an explanatory research design. Data were collected through structured questionnaires distributed to 60 millennial employees selected using purposive sampling. The data were analyzed using multiple linear regression, supported by validity and reliability tests as well as classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests. Results: The findings indicate that mental health, turnover intention, and work environment simultaneously influence employee performance, with partial results showing that work environment and mental health positively affect performance, while turnover intention shows a negative tendency. Novelty: This study integrates psychological and organizational factors to explain employee performance in the banking sector, particularly among millennial employees. Findings: A supportive work environment and good mental health improve employee performance, whereas high turnover intention may reduce performance outcomes. Originality: The originality of this study lies in its empirical focus on millennial banking employees in a regional context, which has received limited attention in prior research. Conclusions: Improving mental health support and work environment quality while managing turnover intention is essential to enheanc employee performance. Type of Paper: Empirical Research Paper.